Respostas
respondido por:
3
x + x² = 90
x² + x - 90 = 0
a = 1
b = 1
c = - 90
Δ = b² - 4.a.c
Δ = 1² - 4.1. (- 90 )
Δ = 1 + 360
Δ = 361
x = - b + - √Δ/ 2a
x = - 1 + - √361/2.1
x = - 1 + - 19/2
x' = 18/2 ⇒ x' = 9
x" = - 20/2 ⇒ x" = - 10
S = { 9 e - 10 }
Os números são : 9 e -10.
x² + x - 90 = 0
a = 1
b = 1
c = - 90
Δ = b² - 4.a.c
Δ = 1² - 4.1. (- 90 )
Δ = 1 + 360
Δ = 361
x = - b + - √Δ/ 2a
x = - 1 + - √361/2.1
x = - 1 + - 19/2
x' = 18/2 ⇒ x' = 9
x" = - 20/2 ⇒ x" = - 10
S = { 9 e - 10 }
Os números são : 9 e -10.
viroriaalves09:
obrigada :)
respondido por:
3
temos a equação do 2 grau:
x2(ao quadrado) + x = 90
x2 + x -90 = 0
delta = 1 - 4(-90)
delta = 361
x' = -1 + 19/ 2 = 18/2 = 9
x'' = -1 - 19/2 = -20/2 = -10
temos estes dois valores q satisfazem o problema :)
x2(ao quadrado) + x = 90
x2 + x -90 = 0
delta = 1 - 4(-90)
delta = 361
x' = -1 + 19/ 2 = 18/2 = 9
x'' = -1 - 19/2 = -20/2 = -10
temos estes dois valores q satisfazem o problema :)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás